LIFTING THE CORPORATE VEIL IN CHINA: STATUTORY VAGUENESS, SHAREHOLDER IGNORANCE AND CASE PRECEDENTS IN A CIVIL LAW SYSTEM. (3rd July 2015) - Hawes, Colin; Lau, Alex K.L.; Young, Angus
Abstract : This article surveys almost 300 court judgments in which shareholders have been sued for corporate debts under Article 20 of the PRC Company Law. The frequency of 'veil-lifting' can indicate how much weight is ascribed in China to fundamental corporate law principles such as limited liability, asset partitioning and the separate legal identity of the corporation. Our survey finds that shareholders were found liable for corporate debts in over 75% of cases, a significantly higher rate of veil-lifting than in jurisdictions elsewhere in the world. We challenge previous scholars' explanations of this phenomenon. We also argue that statutory vagueness has led to unfair and inconsistent veil-lifting judgments in a number of cases. The current interpretative system of Supreme People's Court Regulations and Guiding Cases needs modification to ensure that inconsistencies in adjudication are ironed out in a more timely manner.